PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN MENGGUNAKAN METODE PEMBERIAN TUGAS DI SEKOLAH DASAR NEGERI - Sholihat, Mimi; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to improve reading skills comprehension using assignment methods. This research procedure consists of planning, implementing, observing, and reflecting. The subjects of this study were teacher and third grade students as many as 29 students consisting of 16 male students and 13 female students. Data collection techniques in this research are observing and observing documents. Data analysis techniques in a qualitative descriptive way are used to analyze description data with a simple calculation and the presentation of the average data and the percentage later, then modified in tables and graphs. The results showed that the average score in first cycle is (66.61) increased in cycle II to (88.82) and increased in cycle III to (96.44) with an increase of (29.83). Classical class completeness in cycle I was (71.42%) increased in cycle II to (100%) then in cycle III a very high increase (100%) with an increase of (28.58% It can be concluded that the application of assignment methods can improve the reading comprehension skills of third grade students public elementary school 14 South Pontianak. Keywords: Improvement, giving task, reading skills.